Bispecific Antibodies Progression in Malignant Melanoma - Tang, Juan; Gong, Youling; Ma, Xuelei (Frontiers in Pharmacology, 2022)
The discovery of oncogenes and immune checkpoints has revolutionized the treatment of melanoma in the past 10 years. However, the current PD-L1 checkpoints lack specificity for tumors and target normal cells expressing PD-L1, thus reducing the efficacy on malignant melanoma and increasing the side effects. In addition, the treatment options for primary or secondary drug-resistant melanoma are limited. Bispecific antibodies bind tumor cells and immune cells by simultaneously targeting two antigens, enhancing the anti-tumor targeting effect and cytotoxicity and reducing drug-resistance in malignant melanoma, thus representing an emerging strategy to improve the clinical efficacy. This review focused on the treatment of malignant melanoma by bispecific antibodies and summarized the effective results of the experiments that have been conducted, also discussing the different aspects of these therapies. The role of the melanoma epitopes, immune cell activation, cell death and cytotoxicity induced by bispecific antibodies were evaluated in the clinical or preclinical stage, as these therapies appear to be the most suitable in the treatment of malignant melanoma.